Board Structure and the Profitability of Listed Consumer Goods Firms in Nigeria - Yusufu, Ojochenemi Sunday; Ibrahim, Mohammed Gaddafi; Ali, Abubakar; Sunday Alewo Omale (Eurasian Journal of Management & Social Sciences)
This study investigated the relationship between board structure and the profitability of Listed Consumer Goods Firms in Nigeria. The ex post facto method was used for the study. The study drew on secondary data from twenty (20) listed consumer goods firms in Nigeria as of May 31, 2021. Data was gotten from the annual reports and accounts of the sampled listed consumer goods firms in Nigeria, as well as the stock exchange fact book website from time range (2012 to 2020). Generated data was analyzed using a fixed effect generalized least square (GLS) Multiple linear regression technique and descriptive statistics. The study found that board size (BDS) has a positive (020759) and statistically significant (0.033) relationship with return on asset (ROA) of selected listed consumer goods firms in Nigeria between 2012 and 2020. More also, findings reveal that board independence has a negative (-.3488214) and statistically significant (0.037) relationship with the return on asset of listed consumer goods firms in Nigeria from 2012 to 2020. The study recommended that listed consumer goods firms in Nigeria should maintain the required minimum and maximum size of their board as specified in the Nigeria code of corporate governance. However, it was also recommended that independent directors should possess the necessary skills and expertise relevant to the consumer goods industry.